PARTS OF SPEECH ANALYSIS APPEARED ON HEADLINES NEWSPAPER - Rakhmat Wahyudin Sagala; Tri Indah Rezeki (Serunai : Jurnal Ilmiah Ilmu Pendidikan, 2019)
Newspaper is one kind of mass media that plays a very important role in organizing public opinion. The aim of this study is to analyze the use of parts of speech appeared on headlines of The Jakarta Post Newspaper. Descriptive qualitative research was applied in this study and collected the data from the words on headlines The Jakarta Post Newspaper on November 23rd, 2019 which contain parts of speech. Based on the data result, The Jakarta Post has 11 news headlines. Total words count is 71. Noun, Verbs and Prepositions were frequently used as compared to other parts of speech. Nouns consist of 43 words, Verbs consists of 12 words, Prepositions consist of 10 words, adverbs consist of 3 words, adjectives consist of 2 words, conjunction consists of 1 word and there were no pronoun and interjection found in the headlines of The Jakarta Post newspaper.